BANTUAN IMPLEMENTASI SOFTWARE AKUNTANSI BAGI KARYAWAN MGK - Kristian, Michelle; Klarisa, Livia; Setiyono, Stefani Velisia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
The development of Financial Accounting Standards (SAK) is a framework in the procedure for preparing financial reports so that there is uniformity in the presentation of financial reports. SAK also functions to make it easier for auditors and readers of financial statements to understand and compare the financial statements of different entities, and continue their understanding of knowledge about accounting software that has been given training in the previous semester. The problem faced by MGK is that the results of processing its financial reports are less integrated. The results obtained from this activity are that MGK can use accounting software and produce financial reports that are more accurate and reliable according to Financial Accounting Standards (SAK). so that information from financial reports is less reliable and not timely. In this activity, we provide training assistance and assistance with accounting software implementation.